Comparison of the efficiency of ultraviolet/ultrasonic (UV/US) and ultraviolet/zinc oxide (UV/ZnO) technologies as advanced oxidation processes in the removal of linear alkylbenzene sulfonate (LAS), an anionic detergent, from aqueous media - Tahereh Razavi; Abdolmajid Fadaei (The Journal of Pure and Applied Chemistry Research, 2021)
Surfactants are one of the most commonly found xenobiotics in municipal and industrial wastewater. The purpose of this study was to compare ultraviolet/ultrasonic (UV/US) and ultraviolet/zinc oxide (UV/ZnO) processes in the removal of LAS from aqueous media.In this study, a medium-pressure UV lamp (125 W), an ultrasonic device (400 W and 42 kHz), and ZnO nanoparticles (NPs) were used. The concentration of LAS was 0.5, 14, and 21 mg/L in all experiments. Contact time of 8, 16, and 24 minutes, pH of 3, 7, and 11, and NP concentrations of 50, 100, 150 mg/L were selected. Detergent extraction was performed using methylene blue active substances.The results showed that the efficiency of UV/US process in the removal of LAS was 89.35%, while the removal efficiency of UV/ZnO process was 81.27%. In both processes, the rate of detergent removal increased by elongating the contact time from 8 to 24 minutes. The efficiency of UV/US process in LAS removal was greater than that of the UV/ZnO process. The findings showed that the removal efficiency of UV/US process was directly correlated with pH, while it had an inverse correlation with the removal efficiency of UV/ZnO process.